The role of physiotherapy in menstrual health: a narrative review - Mohammed Abbas, Sayed Arzoo Fatima; Khatavkar, Mayuri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
The field of menstrual health integrates the various aspects of menstrual cycle to enhance overall functioning and quality of life. Physiotherapy plays a key role by providing a comprehensive, evidence-based approach through conservative management strategies. Literature search was performed in the month of September and October 2025 through major academic databases including PubMed, Scopus, Web of Science and Google Scholar. The research included studies from January 2010 until October 2025. The terms used for the study are "menstrual health" and "dysmenorrhea" and "physical therapy" and "premenstrual syndrome" and "endometriosis" and "chronic pelvic pain" and "therapeutic exercise" and "physiotherapy" to find systematic reviews, meta-analyses and randomized controlled trials (RCTs). Existing evidence indicates that physiotherapeutic methods are safe treatment options that can be used with the conventional medical care. Physiotherapy represents a vital yet underutilized approach in the management of menstrual health. Incorporating accessible physiotherapy services into public health strategies will be helpful in reducing treatment gaps while improving menstrual related health care.